LEGAL ASPECTS OF THE USE OF ARTIFICIAL INTELLIGENCE IN TELEMEDICINE-BASED DIAGNOSIS: BETWEEN AID TOOLS MEDICAL AND CLINICAL DECISION MAKING - Kharmaedisyah Putra; Rahmayanti; Donald Rudi Pangaribuan (PT. Radja Intercontinental Publishing, 2026)
The development of Artificial Intelligence (AI) technology in healthcare has encouraged its use in telemedicine-based diagnosis. In Indonesia, the application of AI in telemedicine raises legal questions regarding the status of AI: whether it is merely a medical aid or has become a determinant of clinical decisions. This study aims to analyze the legal aspects of the use of AI in telemedicine by examining the legal framework, the principles of legal responsibility of medical personnel and healthcare facilities, and the ethical implications for the doctor-patient relationship. The research method used is normative juridical with a limited statutory, conceptual, and comparative approach. The results show that based on Law Number 17 of 2023 concerning Health, Law Number 29 of 2004 concerning Medical Practice, and the Minister of Health Regulation concerning the implementation of telemedicine, AI is not yet normatively recognized as a legal subject, but rather as an instrument or aid in the healthcare process. Clinical decisions remain with the physician as the primary person responsible for medical services. However, the high degree of autonomy of AI systems and doctors' reliance on AI recommendations creates a gray area of ​​legal liability, particularly in the case of misdiagnosis or delayed diagnosis. This study recommends the need for specific regulations (lex specialis) regarding medical AI, standards for AI-assisted medical practice, mechanisms for the feasibility and certification of AI devices, and strengthening informed consent that explicitly includes the use of AI in telemedicine services. This will ensure legal certainty, patient protection, and professional accountability in the era of digital transformation in healthcare services.